A Tale of Two Brazzas: Intertwining (Post-)Colonial Namescapes. (2nd January 2019) - Bigon, Liora; Ben Arrous, Michel
Abstract : This article brings together and analyzes two toponyms: Brazzaville Street in Holon, Israel, and Quay of Brazza in Bordeaux, France. In the light of historical and contemporary developments at different points of time, geographies and socio-political contexts, the crisscrossing between both Brazza-related toponyms is useful in promoting a critical and more nuanced interpretation of space and nomenclature. In exploring the varied flows of power, ambiguities and tensions behind the two place names, and in bringing the Congo to the fore, the article also relates to geographies beyond Europe. This aspect of spatial intertwining contributes to the de-Eurocentrization of recent place names studies, which tend to be focused on Europe/the West and on nationalistic aspects. In addition, a variety of primary and secondary materials is employed, including visual and archival sources, and fieldwork.